Truth vibrations – in search of integrity in the literary works and minds - Alicja Trembowski (Filologia Polska, 2021)
What accounts for the value and ethics of a literary work? That words carry energy leads to exerting a powerful impact on those exposed to them. The vibrations of words reflect the soul, which is conditioned by the state of consciousness. Energy, as harmony – is aligned with Truth, Power and the way of Heart, but if in dissonance – it is associated with lack of integrity, disruption and Force. The shape of a text stems from the wave frequency of its creator. And so do the principles of ethics, or moralistic dictum, found in or between the lines, whose nature and spectrum arise from the context that gave roots to the particular awareness rising. Unprecedented in many scientific circles and literary milieus, Consciousness levels can be defined by the calibration technique, owing to the kinesiologic responses of the body muscles. How the procedure of identifying Energy levels occurs, what calibrations the creativity of outstanding poets, novelists and dramatists (including the Nobel Prize laureates) reveals, and what influence it might have on the domain of literature, and a circle of its recipients and experts, are central to this paper.